Effect of CAD/CAM Abutment Morphology on the Outcomes of Implant Therapy: A Randomized Controlled Trial - Barwacz, Christopher A.; Swenson, Madeline; Couso‐Queiruga, Emilio; Comnick, Carissa; Xie, Xian Jin; Avila‐Ortiz, Gustavo (Clinical oral implants research, 2025)
ABSTRACT Objectives Variations in transmucosal abutment contour design may affect the outcomes of implant therapy. This randomized controlled trial was primarily aimed at testing the effect that CAD/CAM zirconia abutments with either a concave or linear divergent transmucosal morphology have on peri‐implant mucosal dynamics and indicators of peri‐implant health at 1 year after final implant‐supported prosthesis insertion in the anterior maxilla. Materials and Methods Following computer‐guided implant placement and osseointegration, eligible subjects were randomized into either the experimental (concave morphology) or the control (linear divergent morphology) group. A comprehensive set of outcomes of interest related to peri‐implant soft tissue dynamics, phenotypical features, and indicators of peri‐implant health were assessed at different time points over a 1‐year period after insertion of the final restoration. Results Out of 60 initially recruited subjects, a total of 54 completed the study (n = 29 in the experimental group concave/n = 25 in the control group). Overall implant survival and restoration rates between master impression and 12 months were 100% and 98.2%, respectively. Although a trend for coronal migration of the buccal mucosa zenith, gain in mucosal thickness, and increased probing depth and bleeding on probing was observed in both groups, these changes were clinically negligible, and no substantial differences were observed between study groups regardless of variations in transmucosal abutment morphology. Conclusion The use of either linear divergent or concave custom CAD/CAM zirconia abutments in a screw‐retained, delayed loading approach yielded no significant differences.